Early diagnosis of congenital Trypanosoma cruzi infection, using shed acute phase antigen, in Ushuaia, Tierra del Fuego, Argentina - Mallimaci, María Cristina (2010)
Chagas' disease, or American trypanosomiasis, is caused by the protozoan parasite Trypanasoma cruzi. It is estimated that 15,000 new cases of congenital T. cruzi transmission occur in the Americas each year. The aim of this study was to estimate the rate of congenital T. cruzi infection in infants born to infected women living in Ushuaia, Argentina, as well to assess a serologic test using Shed Acute Phase Antigen (SAPA) for a timely diagnosis of congenital infection. The rate of congenital infection among children in the study was 4.4% (3/68). Our results show that for infants younger than 30 days of age, matched blood samples from mother and infant were capable of identifying congenital transmission of infection using an enzyme-linked immunosorbent assay with SAPA. For infants older than 3 months, congenital infection could be ruled out using the same procedure